The Evolution of Accounting Information Systems Research: A Bibliometric Analysis of Key Concepts and Influential Authors - Rika Lidyah; Aslichah; Siska Yulia Defitri; Eko Sudarmanto; Arief Yanto Rukmana (The Es Accounting And Finance, 2023)
This research paper provides a comprehensive bibliometric analysis of the evolution of Accounting Information Systems (AIS) research, focusing on key concepts and influential authors. This research uses a systematic data collection process, gathering scientific publications from leading academic databases. Clear inclusion and exclusion criteria were established to select relevant articles for analysis. This methodology uses a variety of bibliometric techniques, including citation analysis, co-citation analysis, keyword analysis, and network analysis, to comprehensively explore the data set. Its findings reveal historical developments and the current state of SIA research, identifying highly cited articles, influential authors, prominent keywords, and collaborative networks. This analysis provides insight into the evolution of key concepts in AIS research and the contributions of influential authors. The results have implications for future research, guide researchers in selecting research areas and promote interdisciplinary collaboration. This research contributes to a better understanding of the trends, patterns, and influential contributors that have shaped the field of AIS.